2021
DOI: 10.1007/s42452-021-04313-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxins in drinking water supply reservoir (Legedadi, Central Ethiopia): implications for public health safety

Abstract: Cyanobacterial blooms in drinking water supply affect its quality, which ultimately impacts ecosystem and public health. Thus, this cross-sectional study was conducted to perform a preliminary study on cyanotoxins via analysis of samples collected only once from two sites during the month of peak algal bloom and to subsequently prompt a comprehensive risk assessment in a major drinking water source, Legedadi Reservoir, of Addis Ababa, the capital city of Ethiopia. Samples were collected during peak algal bloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…High levels of microcystins, ranging from 0.58 to 2.65 μg L −1 , were detected in Lake Tana, Ethiopia [77]. The assessment of microcystin in a major drinking water source, Legedadi Reservoir, of Addis Ababa, Ethiopia recorded levels ranging between 61.63 and 453.89 μg L −1 [78]. The few studies done in Maputo and Gaza provinces indicated the occurrence of microcystin-LR, ranging from 6.83 to 7.78 μg•L −1 [79].…”
Section: Cyanotoxinsmentioning
confidence: 99%
“…High levels of microcystins, ranging from 0.58 to 2.65 μg L −1 , were detected in Lake Tana, Ethiopia [77]. The assessment of microcystin in a major drinking water source, Legedadi Reservoir, of Addis Ababa, Ethiopia recorded levels ranging between 61.63 and 453.89 μg L −1 [78]. The few studies done in Maputo and Gaza provinces indicated the occurrence of microcystin-LR, ranging from 6.83 to 7.78 μg•L −1 [79].…”
Section: Cyanotoxinsmentioning
confidence: 99%